Associations between various possible promoter polymorphisms of MMPs genes and endometriosis risk: a meta-analysis. (October 2016) - Yang, Huijun; Liu, Jiaojing; Fan, Yuanyuan; Guo, Qinghui; Ge, Li; Yu, Na; Zheng, Xuan; Dou, Yanping; Zheng, Shicun
Abstract: Background: Endometriosis is a common, benign gynecological disorder affecting life quality of reproductive-aged women. Several polymorphisms in the promoter regions of the MMPs genes have been reported that were related to endometriosis risk. However, there are many contradictory conclusions, and no meta-analysis focused on this association systematically. Objectives: To evaluate the associations between various possible polymorphisms of MMPs genes and endometriosis risk, and confirm which kinds of MMPs genetic polymorphisms are associated with endometriosis risk, in order to identify the etiology and pathogenesis of endometriosis and the potential effective markers for predicting the predisposition to endometriosis. Search strategy: An exhaustive electronic literature search was conducted, using keywords MMP, endometriosis and SNP, in English and Chinese. Selection criteria: All eligible case-control studies by written in English or Chinese of the associations of MMPs polymorphisms with endometriosis risk, which had sufficient data for examining an odds ratio (OR) with 95% confidence interval (CI), were identified up to March 1, 2015. Data collection and analysis: A total of 1833 patients and 2190 controls from 12 studies were included. Allele frequency differences between cases and controls were performed with the use of odds ratios (ORs) and their respective 95% confidence intervals (CIs) for five genetic models. Main results: For MMP-1 -1607 1G>2G (rs1799750) polymorphism, significant associations were observed both in overall comparison and subgroup analyses based on the stage of endometriosis, ethnicity of each study population and method of genotyping under four genetic models. In contrast, for MMP-2 15918 T>C (rs243847), MMP-2 -753 C>T (rs2285053), MMP-7 -181 A>G (rs11568818), MMP-9 -1562 C>T (rs3918242) and MMP-9 R279Q (rs17576) polymorphisms, no association was found in overall comparison, but in subgroup analyses based on source of control, stage of endometriosis, or ethnicity. Conclusions: MMP-1 -1607 1G>2G polymorphism might modulate risk of endometriosis, so does the MMP-2 15918 T>C, MMP-2 -753 C>T, MMP-7 -181 A>G, MMP-9 -1562 C>T and MMP-9 R279Q polymorphisms in some subgroups.